To find the y-intercept by substitution, substitute #0# for #x# and calculate #y#:

#y = (2/3 xx 0) - 4#

#y = 0 - 4#

#y = -4# Therefore the y-intercept is #-4# or #(0, -4)#

To find the x-intercept by substitution, substitute #0# for #y# and solve for #x#:

#0 = 2/3x - 4#

#0 + color(red)(4) = 2/3x - 4 + color(red)(4)#

#4 = 2/3x - 0#

#4 = 2/3x#

#color(red)(3)/color(blue)(2) xx 4 = color(red)(3)/color(blue)(2) xx 2/3x#

#12/color(blue)(2) = cancel(color(red)(3))/cancel(color(blue)(2)) xx color(blue)(cancel(color(black)(2)))/color(red)(cancel(color(black)(3)))x#

#6 = x#

#x = 6# Therefore the x-intercept is #6# or #(6, 0)#